ПОКАЖЧИК ОСНОВНИХ ПУБЛІКАЦІЙ БРІОЛОГІВ УКРАЇНИ ЗА ОСТАННЄ ДЕСЯТИРІЧЧЯ (2001-2010 рр.) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
ПОКАЖЧИК ОСНОВНИХ ПУБЛІКАЦІЙ БРІОЛОГІВ УКРАЇНИ ЗА ОСТАННЄ ДЕСЯТИРІЧЧЯ (2001-2010 рр.)